Characteristics of Runoff Variation of Heishui River Basin in the Upper Reach of Minjiang River in Changing Environment - WANG Ning; WANG Wensheng; YU Siyi (Renmin Zhujiang)
This paper systematically analyzed the variation characteristics of runoff in the Heishui River Basin,the first tributary on the right bank upstream of Minjiang River,in a changing environment.The variation characteristics of runoff series were studied by using an improved heuristic segmentation algorithm,Mann-Kendall trend test,R/S analysis and wavelet analysis with the runoff data of Shaba hydrological station from 1960 to 2015.The results show the followings:① The abrupt change of annual runoff occurred in 1995.② The annual runoff showed a significant decrease trend with a decreasing rate of 0.32 m3/(s·a) in the past 56 years and may keep the decrease trend in the future.During 1960—1995,the annual runoff showed an insignificant decrease trend with a decreasing rate of 0.12 m3/(s·a),and the period of 1996—2015 witnessed an insignificant increase trend with an increasing rate of 0.80 m3/(s·a).③ Under the influence of environmental changes,the average annual runoff before the change point was larger than that after the point,whereas the inter-annual variation was smaller before the abrupt change.The intra-annual distribution form showed a double-peak curve before 1995 and a single-peak curve after 1995.The intra-annual variation range of runoff was significantly different before and after the change point,which could reduce flood control pressure in the basin but was not conducive to the utilization of water resources in non-flood seasons.④Annual runoff had multi-time-scale variation characteristics.During 1960—2015,the annual runoff had noticeable periods of 6 years,16 years and 28 years.Periods of 7 years and 16 years were found for 1960—1995 and 2 years and 5 years for 1996—2015.